The effect of external stimuli on dreams, as assessed using Q-methodology - Bloxham, Anthony; Durrant, Simon (International Journal of Dream Research, 2014)
Dreams can sometimes incorporate external sensory stimuli (e.g. sounds, smells and physical sensations) into their course and content, either directly or indirectly. This shows that the brain is still able to monitor, process, and perceive what is happening in the surrounding environment during sleep. This study aimed to examine stimulus incorporation in dreams using two auditory stimuli of different languages – one semantically meaningful to participants and one non-meaningful. We hypothesised that participants exposed to the semantically meaningful language would all report similar experiences to each other, and different from those exposed to the non-meaningful language. All participants first spent several weeks improving their dream recall abilities, and then came to the Sleep and Cognition Laboratory at the University of Lincoln for a two hour morning nap, during which a stimulus was played to them in Rapid-Eye-Movement (REM) sleep. They were awoken shortly after to provide a dream report. All dreams contained conversation or speech of some description, but due to participants’ poor verbal memory for dream speech, we could not conclusively say that the stimuli were responsible for this effect. There were, however, at least two dreams with strong evidence to suggest that the stimuli were directly incorporated. Q-Methodology was used to assess similarity of dream experience. This resulted in three distinct factors: (1) calm, consistent, slightly emotional dreams; (2) emotional, normal, understandable dreams; and (3) unstable, inconsistent, unrealistic dreams. The configuration of factors amongst participants did not fully meet the predictions of the hypothesis; however, positive participant feedback on Q-sorting their dream experiences gives promise and potential for the use of Q-Methodology in future dream research. Recommendations and limitations are discussed.